Family-friendly policy and work-family conflict mitigation: the role of work-family boundary negotiation / Hooi-Ching Khor and Azura Abdullah Effendi - Hooi-Ching, Khor; Abdullah Effendi, Azura (Universiti Teknologi MARA, Perlis, 2021)
The family-friendly policy is impossible to fit all working individuals. The circumstance has been revealed in work-family literature which relationship between the policy use and the work-family conflict mitigation has been found inconsistent. Little focus is given in the past studies to ensure the human resource policy is truly useful in meeting individuals' needs. Work, family or both work and family life could be important to individuals. The distinctive life centrality requires individuals to negotiate with the significant others who influence their work and family life arrangements to access and use the preferred and needed family-friendly policy. Boundary management practices seem to be useful for working individuals to reduce work-family conflict. This conceptual paper aims to propose work-family boundary negotiation to buffer the relationship of family-friendly policy use and work-family conflict. Boundary theory is the underlying theory embedded to explain the phenomena. Boundary negotiation style that could be employed for accessing the policy and managing work-family boundary effectively is identified. Future directions and implications for research on negotiation in dealing with the work-family issue are discussed.